El problema de los límites de la lengua ibérica como lengua vernácula (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The problem of the vernacular usage of Iberian language cannot be separated from its function as lingua franca. Both implicate a linguistic situation not identical to the image we get from Iberian epigraphy. We have some sure evidence on parts of Iberian territory where Iberian was spoken and where Iberian was lingua franca. The theory of the NE origin of the Mediterranean variety of Iberian script must be criticised. All these data, together with the archaeological evidence, related to language as another cultural development, make possible for us to propose, as the more economic hypothesis, that Iberian was spoken from an early date in the Alta Andalucía and the SE, without ever arriving as a vernacular to the North of the Ebro neither probably of the river Mijares. In any case its area of use as lingua franca was much wider than its vernacular territory.
Keywords: Iberian language; Iberian culture; Iberian epigraphy; Iberian writing; spoken versus written language; lingua franca; origins